Association of Fruit and Vegetable Consumption During Early Adulthood With the Prevalence of Coronary Artery Calcium After 20 Years of Follow-Up: The Coronary Artery Risk Development in Young Adults (CARDIA) Study. Issue 21 (24th November 2015) - Miedema, Michael D.; Petrone, Andrew; Shikany, James M.; Greenland, Philip; Lewis, Cora E.; Pletcher, Mark J.; Gaziano, J. Michael; Djousse, Luc
Abstract : Background—: The relationship between intake of fruits and vegetables (F/V) during young adulthood and coronary atherosclerosis later in life is unclear. Methods and Results—: We studied participants of the Coronary Artery Risk Development in Young Adults (CARDIA) study, a cohort of young, healthy black and white individuals at baseline (1985–1986). Intake of F/V at baseline was assessed using a semiquantitative interview administered diet history, and coronary artery calcium was measured at year 20 (2005–2006) using computed tomography. We used logistic regression to adjust for relevant variables and estimate the adjusted odds ratios and 95% confidence intervals across energy-adjusted, sex-specific tertiles of total servings of F/V per day. Among our sample (n=2506), the mean (SD) age at baseline was 25.3 (3.5) years, and 62.7% were female. After adjustment for demographics and lifestyle variables, higher intake of F/V was associated with a lower prevalence of coronary artery calcium: odds ratio (95% confidence interval) =1.00 (reference), 0.78 (0.59–1.02), and 0.74 (0.56–0.99), from the lowest to the highest tertile of F/V, P value for trend <0.001. There was attenuation of the association between F/V and coronary artery calcium after adjustment for other dietary variables, but the trend remained significant: odds ratio (95% confidence interval): 1.00 (reference), 0.84 (0.63–1.11), and 0.92 (0.67–1.26), P value for trend <0.002]. Conclusions—: In this longitudinal cohort study, higher intake of F/V during young adulthood was associated with lower odds of prevalent coronary artery calcium after 20 years of follow-up. Our results reinforce the importance of establishing a high intake of F/V as part of a healthy dietary pattern early in life.